Auditory-motor interactions during speech perceptions and production - Tang, D-L (2020)
Speech perception and production are two central aspects of human language. It remains unclear, however, how sensory and motor systems interact with each other during these two processes. The overall aim of this thesis was to investigate auditory-motor interactions during both speech perception and production.